FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TURNOVER INTENTION PERAWAT DI RUMAH SAKIT PERMATA DEPOK TAHUN 2019 - Lisnawati; Sarah Handayani; Muhammad Bigwanto (Prosiding Seminar Nasional Berseri, 2020)
Abstract.Turnover intention is the intention of someone to move and leave the organization and look for other job. Turnover intention can be a turnover predictor. This research was conducted for in Permata Depok Hospital, there were problems related to the turnover intention of nurses (>10%). The purpose of this study was to determine the factors associated with nurse turnover intention at Permata Depok Hospital in 2019. Measurements in this study consisted of individual characteristics (age, sex, marital status, education level, employment status, years of service) and satisfaction employment toward compensation, employment, supervision, career development, co-workers, and organizational policies. This research is a quantitative study using cross sectional design. The population of this study were all nurses who actively worked at Permata Depok Hospital until August 2019 total of 103 nurse as the research sample. Data collection was conducted during June-August 2019. Data analysis used univariate and bivariate analysis in the form of chi-square test. The results of the bivariate analysis showed that of the 12 variables, there were 2 variables which had a significant relationship, namely the satisfaction variable towards compensation and satisfaction with work with p-value < 0.05. In this study nurses who had intention to leave (turnover intention) amounted to 39 nurses (37.9%). It was suggested to the hospital management to pay attention and increase job satisfaction for nurses in order to reduce nurse turnover intention.